Relationship between C-reactive protein and features of the metabolic syndrome in military pilots in the Serbia and Montenegro - Jovelić Aleksandra; Rađen Goran; Jovelić Stojan; Marković Marica (Vojnosanitetski Pregled)
Background/Aim. C-reactive protein is an independent predictor of the risk of cardiovascular events and diabetes mellitus in apparently healthy men. The relationship between C-reactive protein and the features of metabolic syndrome has not been fully elucidated. To assess the cross-sectional relationship between C-reactive protein and the features of metabolic syndrome in healthy people. Methods. We studied 161 military pilots (agee, 40±6 years) free of cardiovascular disease, diabetes mellitus and active inflammation on their regular annual medical control. Age, total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol, triglycerides, fasting glucose, glycosylated hemoglobin, blood pressure, smoking habit, waist circumference and body mass index were evaluated. Plasma C-reactive protein was measured by the immunonephelometry (Dade Behring) method. Metabolic syndrome was defined according to the National Cholesterol Education Program Expert Panel. Results. The mean C-reactive protein concentrations in the subjects grouped according to the presence of 0, 1, 2 and 3 or more features of the metabolic syndrome were 1.11, 1.89, 1.72 and 2.22 mg/L, respectively (p = 0.023) with a statistically, significant difference between those with 3, and without metabolic syndrome (p = 0.01). In the simple regression analyses C-reactive protein did not correlate with the total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol, body mass index and blood pressure (p > 0.05). In the multiple regression analysis, waist circumference (β = 0.411, p = 0.000), triglycerides to high density lipoprotein cholesterol ratio (β = 0.774, p = 0.000), smoking habit (β = 0.236, p = 0.003) and triglycerides (β = 0.471, p = 0.027) were independent predictors of C-reactive protein. Conclusions. Our results suggested a cross-sectional independent correlation between the examined cardiovascular risk factors as the predominant features of metabolic syndrome and C-reactive protein in the group of apparently healthy subjects. The lack of correlation of C-reactive protein with the total cholesterol and low density lipoprotein cholesterol in our study may suggest their different role in the process of atherosclerosis and the possibility to determine C-reactive protein in order to identify high-risk subjects not identified with cholesterol screening.